Viral infection of the marine alga Emiliania huxleyi triggers lipidome remodeling and induces the production of highly saturated triacylglycerol. Issue 1 (9th February 2016) - Malitsky, Sergey; Ziv, Carmit; Rosenwasser, Shilo; Zheng, Shuning; Schatz, Daniella; Porat, Ziv; Ben‐Dor, Shifra; Aharoni, Asaph; Vardi, Assaf
Summary: Viruses that infect marine photosynthetic microorganisms are major ecological and evolutionary drivers of microbial food webs, estimated to turn over more than a quarter of the total photosynthetically fixed carbon. Viral infection of the bloom‐forming microalga Emiliania huxleyi induces the rapid remodeling of host primary metabolism, targeted towards fatty acid metabolism. We applied a liquid chromatography‐mass spectrometry (LC‐MS)‐based lipidomics approach combined with imaging flow cytometry and gene expression profiling to explore the impact of viral‐induced metabolic reprogramming on lipid composition. Lytic viral infection led to remodeling of the cellular lipidome, by predominantly inducing the biosynthesis of highly saturated triacylglycerols (TAGs), coupled with a significant accumulation of neutral lipids within lipid droplets. Furthermore, TAGs were found to be a major component (77%) of the lipidome of isolated virions. Interestingly, viral‐induced TAGs were significantly more saturated than TAGs produced under nitrogen starvation. This study highlights TAGs as major products of the viral‐induced metabolic reprogramming during the host–virus interaction and indicates a selective mode of membrane recruitment during viral assembly, possibly by budding of the virus from specialized subcellular compartments. These findings provide novel insights into the role of viruses infecting microalgae in regulating metabolism and energy transfer in the marine environment and suggest their possible biotechnological application in biofuel production.